Multimodality liver directed treatment for colorectal liver metastasis: Array of complementary options can improve outcomes - A single centre experience from India - Patkar, Shraddha; Chopde, Amit; Shetty, Nitin; Kulkarni, Suyash; Gala, Kunal Bharat; Chandra, Daksh; Ramaswamy, Anant; Ostwal, Vikas; Goel, Mahesh (Frontiers in Oncology, 2023)
AIM: Complimentary use of Liver directed therapies (LDTs) with systemic chemotherapy has improved oncologic outcomes in colorectal liver metastasis (CRLM). We analysed institutional results of multimodality management. Methods: Retrospective analysis of prospectively maintained database of CRLM patients managed with LDT including surgical resection, Ablation, Transarterial chemoembolization (TACE) or Transarterial radioembolization (TARE) between November 2009 to March 2020 was performed. Management plan was decided in multidisciplinary meeting. Resectable tumours underwent surgical resection or ablation or both in some cases. Borderline resectable or unresectable disease was treated with down staging chemotherapy or TACE/TARE followed by resection or ablation. All patients received adjuvant chemotherapy. Factors influencing survival were analysed. Results: Out of total 388 patients, surgery alone was done in 196(50.57%) patients while surgery with other LDT in 28(7.2%). Ablation alone was done in 102(26.2%); TACE/TARE were done as standalone treatment in 22(5.6%) and 10(2.5%) cases respectively. TACE + ablation was done in 28(7.2%). 5-year Overall Survival(OS) was 49.8% while Event free survival(EFS) was 21.4%. The OS and EFS for surgical group was significantly better than non-surgical group (78 V/s 39 months and 20 V/s 15 months p <0.005). The resectable (78 months) group had better OS as compared to borderline resectable and Unresectable group (39 months and 29 months). Female gender, unilobar distribution, resectability and surgery were associated with improved OS. Conclusion: Although surgery remains the mainstay of treatment, complementary use of non-surgical LDT with systemic therapy offers possibility of good outcomes in advanced liver limited disease. Our experience highlights the impact of multidisciplinary care in optimizing CRLM treatment.